The Effect of The Total Value Of Exports, Imports and Economic Growth on Exchange Rate With State Governance As a Variable Moderating In Southeast Asia 2009-2019 - Murady, Iklimah; Oktarina, Kurnia; Ghafur, Muhammad; Wau, Taosige; Umam, Khotibul (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
The purpose of this study is to determine the effect of independent variables such as exports, imports, and economic growth on the dependent variable in the form of the exchange rate by using the variable of state governance as a moderating variable. The data used is panel data The population of this study is a Southeast Asian country. The sampling technique in this study was taken using purposive sampling. Data analysis in this study used the Chow, Housman, and MRA test analysis methods using Stata13 software. The results are based on the best Random Effect Model (REM) model, that is, there is no significant effect of exports and imports on the exchange rate Meanwhile, economic growth, and state governments have a significant effect on the exchange rate based. However, based on the MRA test, the variable of state governance strengthens the relationship between these three variables (exports, imports, and economic growth) on the exchange rate.